Pediatric routine vaccinations in the COVID 19 lockdown period: the survey of the Italian Pediatric Society - Rocco Russo; Elena Bozzola; Paolo Palma; Giovanni Corsello; Alberto Villani (BMC, 2021)
Abstract Background COVID-19 pandemic was responsible for disrupting routine immunization activities all over the world. Aim of the study was to investigate the reduced adherence to the national children vaccination schedule during the lockdown period in Italy. Materials and methods Through social channels, the Italian Pediatric Society conducted a survey among Italian families on children vaccination during lockdown period. Results In the study period, 1474 responders were collected. More than one third (34%) of them skipped the vaccine appointment as they were afraid of SARS-CoV-2-virus (44%), vaccination services postponed the appointment (42%) or was closed to public (13%). Discussion Reduction in routine immunization coverage may represent a serious life-threating problem for unvaccinated or under-vaccinated children. Conclusions Information on national and local preventive measures including physical distancing, handwashing, and proper coughing/sneezing hygiene should be spread among families in order to contrast vaccine hesitancy and maintain adequate coverage levels during COVID19 pandemic period.